1046. Week 48 Outcomes from the BRAAVE 2020 Study: A Randomized Switch to B/F/TAF in African American Adults with HIV. (31st December 2020) - Hagins, Debbie; Kumar, Princy; Saag, Michael; Wurapa, Anson K; Brar, Indira; Berger, Daniel; Osiyemi, Olayemi; Hileman, Corrilynn; Ramgopal, Moti; McDonald, Cheryl; Blair, Christiana; Andreatta, Kristen; et al.
Abstract: Background: Black Americans are disproportionately impacted by HIV. The BRAAVE 2020 study, evaluated the safety and efficacy of switching to the guidelines-recommended single-tablet regimen bictegravir, emtricitabine, tenofovir alafenamide (B/F/TAF) in Black adults through week (W) 48. Methods: Adults with HIV who self-identified as Black or African American and were virologically suppressed on 2 NRTIs plus a 3 rd agent were randomized (2:1) to switch to open-label B/F/TAF once daily or stay on their baseline regimen (SBR). Prior virologic failure was allowed except failure on an INSTI. Prior resistance to NNRTIs, PIs and/or NRTIs was permitted except K65R/E/N, ≥3 thymidine analog mutations or T69-insertions. Primary INSTI-resistance was excluded. SBR participants switched to B/F/TAF at W24. Efficacy was assessed at the W24 (1 ○ endpoint, noninferiority margin 6%) and at W48 as the proportion with HIV-1 RNA ≥ 50 c/mL by FDA Snapshot and by changes in CD4 count. Safety was assessed by adverse events (AE) and lab results. Results: 495 were randomized and treated (B/F/TAF n=330, SBR n=165): 32% cis women, 2% transgender women, median age 49 y (range 18-79), 10% had pre-existing M184V/I mutation (Table 1), and 62% lived in the US South. At W24, 1% (2/328) on B/F/TAF vs 2% (3/165) on SBR had HIV-1 RNA ≥50 c/mL (difference -1.2%; 95% CI -4.8% to 0.9%) demonstrating noninferiority of B/F/TAF; 2 with pre-existing primary INSTI resistance were excluded from analysis. 163 assigned to SBR completed W24 and switched to B/F/TAF (SBR to B/F/TAF). At W48 1% (3/328) originally randomized to B/F/TAF and 0 SBR to B/F/TAF had HIV-1 RNA ≥ 50 c/mL (Table 2). The presence of baseline NRTI resistance did not affect the efficacy of B/F/TAF. No treatment emergent resistance was detected. The mean (SD) changes in CD4 were +7 cells/mm 3 (189) for B/F/TAF and -8 cells/mm 3 (159) for SBR to B/F/TAF. Median (IQR) weight increased 0.9 kg (-1.5, 4.1) and 0.6 kg (-1.0, 3.1) for B/F/TAF and SBR to B/F/TAF groups, respectively. Study drug-related AEs occurred in 10% of participants while on B/F/TAF; most were grade 1. Table 1. Table 2. Conclusion: Switching to B/F/TAF was highly effective for Black adults regardless of baseline regimen or pre-existing NRTI resistance and was associated with few treatment related AEs or discontinuations. Disclosures: Debbie Hagins, MD, Gilead Sciences Inc. (Consultant, Grant/Research Support, Scientific Research Study Investigator, Advisor or Review Panel member)Janssen (Grant/Research Support)Merck (Consultant, Grant/Research Support, Advisor or Review Panel member)Viiv Healthcare (Consultant, Grant/Research Support, Advisor or Review Panel member) Princy Kumar, MD, Gilead Sciences Inc. (Scientific Research Study Investigator) Michael Saag, MD, Gilead Sciences Inc. (Consultant, Grant/Research Support, Scientific Research Study Investigator)Merck (Consultant, Grant/Research Support)Proteus (Grant/Research Support)Viiv Healthcare (Consultant, Grant/Research Support) Anson K. Wurapa, MD, Gilead Sciences Inc. (Grant/Research Support, Scientific Research Study Investigator, Advisor or Review Panel member)GlaxoSmithKline (Grant/Research Support)Janssen (Grant/Research Support, Advisor or Review Panel member)Pfizer (Grant/Research Support) Indira Brar, MD, Gilead (Speaker's Bureau)janssen (Speaker's Bureau)ViiV (Speaker's Bureau) Daniel Berger, MD, Gilead Sciences Inc. (Scientific Research Study Investigator) Olayemi Osiyemi, M.D, GlaxoSmithKline (Advisor or Review Panel member, Speaker's Bureau)ViiV Healthcare (Advisor or Review Panel member, Speaker's Bureau) Corrilynn Hileman, MD, Gilead Sciences Inc. (Consultant, Scientific Research Study Investigator) Moti Ramgopal, MD FACP FIDSA, AbbVie (Speaker's Bureau)Allergan (Speaker's Bureau)Gilead Sciences Inc. (Consultant, Scientific Research Study Investigator, Speaker's Bureau)Janssen (Speaker's Bureau)Merck (Consultant)Viiv Healthcare (Consultant) Cheryl McDonald, MD, Gilead Sciences Inc. (Grant/Research Support, Scientific Research Study Investigator, Speaker's Bureau)Janssen (Grant/Research Support)Merck (Grant/Research Support, Speaker's Bureau)Viiv Healthcare (Grant/Research Support) Christiana Blair, MS, Gilead Sciences (Employee, Shareholder) Kristen Andreatta, MSc, Gilead Sciences (Employee, Shareholder) Sean E. Collins, MD, MS, Gilead Sciences (Employee) Diana M. Brainard, MD, Gilead Sciences (Employee) Hal Martin, MD, MPH, Gilead Sciences Inc. (Employee, Shareholder)